Rola HRM i kultury organizacyjnej w procesach przejęć i fuzji przedsiębiorstw - Zając, Czesław (The Role of HRM and Organizational Culture in the Processes of Mergers and Acquisitions (M&A) of Enterprises, 2008)
Results of the empirical research and study of publications done by the author indicate the growing significance of HRM and organizational culture in the management of M&A of enterprises. They also confirm the fact that appriopriate personal strategy is the key for success of the ownership transformation. This strategy is "operationalized" in the form of different tasks in the rangę of personal function which are supported by HRM methods and instruments. Organizational culture has to be taken into consideration as well. Managerial ability of solving problems of social, organizational and cultural character in the processes of M&A is very important too. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 264-273